Framework to build component-based e-manufacturing (production module) / Liew Hoi Ming - Liew, Hoi Ming (2004)
E-Manufacturing system is a large system that comprises of various modules such as sales, production, material management, financial, scheduling and so on. Most of the system are usually customize based on the manufacturer needs. In nature, e-Manufacturing system is divided into stand-alone application and web application. This project is to build a framework to develop a component-based e-Manufacturing system. A group of four members are assigned to run this project. This proposed system consists of four main modules such as Sales, MRP, Production, and Material Management. The framework should be embedded with important components. The essence of the framework is able to support reusable approach where it is a hot trend in software development. Apart from that, framework should be extensible and scalability due to rapid business requirement changes. In order to enhance the system efficiency, robustness and able to meet the user requirements, existing e-Manufacturing systems have been reviewed and analysis in depth. Besides that, some of researches have been done the latest technologies such as development environment or tools DBMS assemblies and so on. A combination of incremental and iterative model development approach has been chosen to develop the framework. There are some substantial reasons that advocate this approach that who be ideal for this project development. Unified Modelling Language (UML) is being used to illustrate or visualize the functional and non-functional requirements for the system. Class diagram is used to illustrate the design of the database